Multiple pulmonary artery aneurysms in tuberous sclerosis complex. (21st January 2013) - Dunet, Vincent; Qanadli, Salah Dine; Lazor, Romain; Beigelman-Aubry, Catherine
Abstract : Tuberous sclerosis complex (TSC) is a rare genetic disorder characterised by multiple hamartomas, caused by inactivating mutations of the TSC1 / TSC2 tumour suppressor genes. Classical pulmonary involvement in tuberous sclerosis complex (TSC) consists of lymphangioleiomyomatosis and/or multiple micronodular pneumocyte hyperplasia (MMPH). Association of TSC with pulmonary artery aneurysm (PAA) has been only exceptionally described. We report here the first case of TSC with multiple PAA in combination with MMPH, cardiac rhabdomyomas and bone, skin and brain involvement.